Curated Learning Paths for Faculty Upskilling in STEM Disciplines: An Institutional Best Practice - Gupta, Ankur; Sawhney, Sahil; Nanda, Ankita; Gupta, Adit (Journal of Engineering Education Transformations, 2026)
India’s rapid economic growth necessitates a higher education system adept at training students in emerging technologies, yet the scarcity of high-quality STEM faculty poses a significant challenge. This quantitative case study, conducted over two years at an Indian STEM institution, investigates the impact of formulating and implementing curated learning paths on faculty upskilling. Formulated through a consultative process aligned with institutional strategy, these learning paths incorporated courses/certifications from Coursera and Swayam, industry practitioner-led training and paid workshops to build competencies in emerging technologies. Tracking Learning and Development (L&D) outcomes, the study assessed 59 faculty members’ competency acquisition, course delivery effectiveness and higher-order outcomes (research, institutional reputation, student learning experiences). Paired t-tests and regression analysis revealed a significant increase in faculty competency and course delivery effectiveness, with a strong correlation between tracking and performance improvements. Its impact on higher-order outcomes, including Scopus/WoS-indexed publications and institutional reputation, were also examined. The findings highlight the effectiveness of curated learning paths in bridging faculty talent gaps and driving the achievement of critical institutional outcomes.